Effectiveness of a groundsill structure in reducing scouring problem at Cimadur River, Banten Province. Issue 1 (October 2021) - Fitri, Arniza; Yao, Li; Pratiwi, Dian; Phelia, Arlina; Susarman,; Dewantoro, Fajar; Safitri, Destiana; Maulud, Khairul Nizam Abdul
Abstract: Groundsill is a transverse threshold structure that can be built on water body as one alternative in reducing the upstream water velocity and therefore could maintain the upstream sedimentation rates. Due to scouring problems faced in the Cimadur River, Banten Province, a groundsill structure has been constructed at one location in Cimadur River which is near to the Bantar Karang bridge structure. The scouring problem is worried to damage the abutment of the bridge structure. This study aims to investigate the effectiveness of the groundsill structure in reducing the scouring problem in Cimadur River, Banten Province. The effectiveness is determined by comparing the riverbed elevation around the Bantar Karang bridge structure, before and after 5 months construction of the groundsill structure. The results showed that the presence of the groundsill structure has increased the riverbed elevation especially around the abutment of the Bantar Karang bridge (approximately 25 cm in average after 5 months installation of the groundsill structure). It is therefore can slowly reduce the local scouring problem around Bantar Karang bridge. Besides, the results also showed that there is small reduction of riverbed elevation at the downstream area of the groundsill structure approximately about 10 cm in average. It can be concluded that the groundsill structure is quite effective in reducing the local scouring problem in Cimadur River, especially upstream area of their structure around Bantar Karang bridge.